Methodology for assessing the contribution of knowledge services during the new product development process to business performance. (1st April 2021) - Choi, Jeongsub; Kim, Byunghoon; Han, Chang Hee; Hahn, Hyuk; Park, Hun; Yoo, Jaeyoung; Jeong, Myong Kee
Highlights: Contributions of knowledge-intensive services in new product development are assessed. Variables from the services across new product development stages are correlated. Variable importance is assessed alleviating the correlation effect among variables. A case of the services from a public research organization in Korea was studied. Abstract: Knowledge intensive service (KIS) is a key resource for new product development (NPD) of a firm. As a KIS provider, public research organization plays a critical role in supporting the success of firms' NPD process, thereby promoting national/regional/local economic growth. In this study, we examine the contribution of KISs at stages in an NPD process to firms' performance considering the correlations between input variables. For the explicit quantification of the contributions at the NPD stages, we propose a novel methodology using a variable importance assessment method. In doing so, the proposed method alleviates the correlation effects and facilitates a direct interpretation of the importance of input variables. The proposed methodology is evaluated in the case of a public research organization in South Korea, using a survey dataset collected from Korean small and medium-sized firms. The empirical results show that, with the inter-stage correlations, KISs differently contribute to firms at the NPD stages depending on performance measures: KISs mostly at the both-end NPD stages assist firms' managerial decision-making, and KISs at all the stages except for product implementation help firms save time and cost.